2000
DOI: 10.1054/jhsb.2000.0432
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound for Diagnosis of Scaphoid Fractures

Abstract: We investigated the diagnostic value of two different ultrasound scanning methods for the early diagnosis of acute scaphoid fractures. Fifty-seven patients with ten scaphoid fractures were assessed within a week of injury. The accuracy of the ultrasound assessment was 84% and its specificity was 91%. However, its sensitivity was only 50%. We conclude that ultrasound examination is unreliable for the diagnosis of acute scaphoid fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 11 publications
1
17
0
3
Order By: Relevance
“…46,[83][84][85][86][87] The reported criterion standards included x-rays within 14 days, 83,84 CT within 3 days, 86,87 or MRI. 46 All studies used US obtained and interpreted by musculoskeletal radiologists.…”
Section: Usmentioning
confidence: 99%
See 1 more Smart Citation
“…46,[83][84][85][86][87] The reported criterion standards included x-rays within 14 days, 83,84 CT within 3 days, 86,87 or MRI. 46 All studies used US obtained and interpreted by musculoskeletal radiologists.…”
Section: Usmentioning
confidence: 99%
“…46 All studies used US obtained and interpreted by musculoskeletal radiologists. Munk et al 83 used a mechanical annular array 7.5-MHz high-resolution scanner to image the cortex of the scaphoid, as well as a 5-to 10-MHz Doppler scanner to evaluate the displacement of the radial artery from the radial cortex of the scaphoid. Herneth et al 46 used a high-spatial-resolution 10.5-MHz linear array probe with a standoff pad placed over the wrist to increase spatial resolution.…”
Section: Usmentioning
confidence: 99%
“…There are a few studies evaluating ultrasound as an initial imaging modality. In one study by Munk et al, ultrasound examinations performed in an orthopedic clinic had a sensitivity of 50% and specificity of 91% when compared to radiograph performed on the day of the clinic visit and at 10-14 day follow up [19]. In an ED population, one study found pointof-care ultrasound to have a sensitivity of 78% and a specificity of 89% when compared to radiograph performed on presentation then every month thereafter as long as the patient continued to be symptomatic [20].…”
Section: Scaphoid Fracturementioning
confidence: 99%
“…L'échographie est une technique non invasive mais elle n'a pas encore fait la preuve de sa fiabilité pour le diagnostic précoce des fractures occultes [54]. Le critère le plus spéci-fique étant la rupture de la corticale [55].…”
Section: Les Ultrasonsunclassified